The moderating effect of the internal ownership on the relationship between the effectiveness of Board of Directors and Executive Compensation with earnings management in the Amman Stock Exchange - Anas Najeed Mosa, Ghazalat (Universiti Malaysia Perlis (UniMAP), 2017)
Doctor of Philosophy in Accounting